Simulation of the Performance of CdTe/CdS/ZnO Multi- Junction Thin Film Solar Cell - O, Shoewu; G, Anuforonini; O, Duduyemi (Review of Information Engineering and Applications, 2016)
Multi-junction solar cell layers containing CdTe/CdS/ZnO photovoltaic cells were created using SCAP 1D software using parameters based on the previous theoretical characterization to determine the significance effect on the optimization in terms of efficiency on the solar cell. The simulation of the models were carried out by varying the band gap and thickness of the absorber layer and subsequently formulate model equation using regression analysis to determine the efficiency and fill factor at any given value. Result shows that increase in the thickness of absorber layer increases fill factor, current density and open voltage from 83.74- 84.77, 26.26 -28.85mA/cm2, 0.71- 0.73, 15.51 -17.82% that ultimately resulted in a high efficiency of solar cell while increase in band-gap of the absorber layer reduces efficiency of the solar cell. Model equation gives errors ranges between 0.026 – 0.4 for thickness and efficiency, 0.0068 – 0.078 for thickness and fill factor and 0.003 – 0.2 for band gap and efficiency. The study shows that large thickness of absorber layer and low band gap favor the optimization and model equations can be used to estimate/forecast the efficiency and fill factor within the limit of the variable parameters and this offers better direction for laboratory experiment.